FORMULASI DAN UJI AKTIVITAS SEDIAAN TRANSDERMAL PATCH EKSTRAK BIJI RAMBUTAN (Nephelium lappaceum L) TERHADAP TIKUS PUTIH JANTAN (Rattus norvegicus strain wistar) SEBAGAI ANALGETIK - Srie Rezeki Nur Endah; Elin; Ali Nofriyaldi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
The rambutan plant has anti-pain characteristics based on empirical evidence. Flavonoids, tannins, and saponins, which are known to have analgesic effect, are found in rambutan seeds. The purpose of this study was to assess the analgesic effectiveness of rambutan seed extract transdermal patch formulation and the most effective dose for male white rats. The maceration process with 70% ethanol is used to extract rambutan seeds for the research. Analgesic activity testing was performed on 25 male white mice divided into five groups, with group 1 serving as a negative control and receiving a 1% Na-CMC patch. Group II, as a positive control or comparison, was applied with Salonpas Pain Relief Patch 10%. Group III: As a test dose, I was attached to a patch of rambutan seed extract with a concentration of 1%. Group IV, as test dose II, had a patch of rambutan seed extract with a concentration of 2% applied to it. Group V, as test dose III, had a patch of rambutan seed extract with a concentration of 4% applied to it. The test preparation was administered transdermally, while 1% acetic acid was administered intraperitoneally 15 minutes after administration of the test preparation. Observe the stretching process every 5 minutes for 60 minutes. The research results on the analgesic activity of the test doses were 83.50%, 93.81%, and 42.26%, respectively. These results show that the most effective dose is dose II with a concentration of 2%.